2020
DOI: 10.3389/fneur.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback Core Exercise Using Hybrid Assistive Limb for Physical Frailty Patients With or Without Parkinson's Disease

Abstract: Introduction: Elderly people often exhibit "frailty," and motor dysfunction occurs. Several studies have reported about the relationship between motor dysfunction and frailty in Parkinson's disease (PD). This study aimed to test whether the core exercise using the hybrid assistive limb lumbar type for care support (HAL-CB02) may improve the motor functions in frailty patients with or without PD and to explore the optimal patient selection from the frailty cohort. Materials and Methods: We recruited 16 frailty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…To date, several reports have shown that exercise therapy using the HAL lumbar type improved physical functions in the elderly. Kotani et al [20] reported that five core and squat exercise sessions with the HAL lumbar type for frailty improved motor function, including TUG times. Miura et al [19] found that balance function improved after 12 sessions of exercise therapy with the HAL lumbar type consisting of sitto-stand, lumbar flexion-extension, and gait training for the locomotive syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several reports have shown that exercise therapy using the HAL lumbar type improved physical functions in the elderly. Kotani et al [20] reported that five core and squat exercise sessions with the HAL lumbar type for frailty improved motor function, including TUG times. Miura et al [19] found that balance function improved after 12 sessions of exercise therapy with the HAL lumbar type consisting of sitto-stand, lumbar flexion-extension, and gait training for the locomotive syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been considered that support for hip extension movements by the HAL lumbar type may also be effective in supporting the standing movement. To date, robotic rehabilitation using the HAL lumbar type has been attempted for locomotive syndrome [19] and frailty [20]. However, few studies have focused on postoperative rehabilitation in hip fracture patients using the HAL lumbar type.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, a few clinical studies have reported on the robotic-assisted exercise therapy for locomotive syndrome. Kotani et al [ 31 ] firstly reported core exercise and squat exercise using the lumbar type HAL showed significant improvement of motor function in 16 frailty patients including 8 Parkinson’s disease (PD) patients and 8 non-PD patients with spine problems. In this study, three kinds of training including sit-to-stand training, lumbar flexion–extension training, and gait training were performed by using the lumbar type HAL for 33 locomotive syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that overload might be avoided during exercise by using the lumbar-type HAL in this case, resulting in sufficient training. Moreover, Kotani et al [ 14 ] reported that motor functions evaluated by 10MWT and TUG improved after core exercises and squats with the use of the lumbar-type HAL in elderly patients with physical frailty. The lumbar-type HAL might be a treatment option for physical frailty even when complicated by spinal problems.…”
Section: Discussionmentioning
confidence: 99%